"This is not a Drill—Evacuate the Building Now!": Disaster Preparedness at the Outpatient Surgery Department: An Experiential Lesson. Issue 2 (April 2020) - Burnett, Ann Lacy; McGuire, Koren
Abstract: This article describes an actual disaster that took place at an outpatient surgical center. Reported are the context of the disaster, the potential dangers, the unprepared reactions of the staff, and the following leadership shown by the staff nurses and clinical nurse specialist in response to the disaster. Described is the didactic education they created, with a tabletop evacuation drill and a hands-on exercise presented to the whole multidisciplinary staff. Participants were given a pre- and posteducation survey to assess the effectiveness of the training. Results showed that staff felt far more confident and prepared to deal with a disaster and evacuation after the didactic education combined with the hands-on exercises. Our findings suggest that a training that uses minimal time, space, and resources can significantly improve confidence and preparedness in staff. Also identified was the need for changes in our existing policy to be modeled on logistics that correspond with an actual disaster and evacuation.